The role of culture in acceptance of technology evolution among administrative support personnel in Maran, Pahang Darul Makmur / Hazlin Hasan...[et. al.] - Hasan, Hazlin; Syed Wahid, Sharifah Norhuda; Jais, Mohammad; Nikman, Khairunnisa (Universiti Teknologi MARA Cawangan Pahang, 2013)
The development of various technologies has affected the environment, human societies and science. Technology evolution has become a big challenge and may change at many levels in the organization either government or private sectors. This acceptance of technology is much influenced by the dimensions of culture; uncertainty avoidance, power distance, individualism-collectivism and masculinity-femininity, defined by everything from language and religion to cuisine, social habits, music and arts. Thus, this study focuses on the role of culture in the acceptance of technology among administrative support personnel employed in the government office, as the organizations depend heavily on them in running their daily operations. It is hoped that the findings of this study will provide useful information in improving the acceptance level of technology evolution at many levels in the organization. 75 respondents were selected and the relationship between dimensions of culture and acceptance of technology evolution was found to be moderate and positive. Future research can be conducted to examine other factors that may have a significant effect towards acceptance of technology evolution so that job performance can be increased.